GAMBARAN RISIKO DAN UPAYA PENCEGAHAN STUNTING PADA PERIODE KEHAMILAN DIDAERAH ALIRAN SUNGAI - Yulia Irvani Dewi; Agrina Agrina; Erika Erika (Jurnal Ners Indonesia, 2023)
Pre-conception and conception were critical period of growth and development of fetus in utero. Restricted intrauterine growth is at great risk of remaining stunted. This study aimed to determine the risk factors of stunting and behavioral factors of pregnant women during pregnancy in the Siak River. Method: the research design used was a convergent parallel design or concurrent mixed methods. A total of 100 respondents of pregnant women as respondents were taken by purposive sampling and 15 participants. A questionnaire, question tools, and environmental observation checklists were used to collect data. A descriptive survey and thematic analysis were selected to identify the predictors and factors associated preventing stunting during pregnancy. Result: the majority of respondents were aged 20-35 years (83%), the level of education was senior high school (63%), a housewife (89%), Minang tribe (40%), Muslim (95%), and had height > 145 cm (99%). The description of the risk factors for stunting in the pregnancy period was respondent who has a height of ≤ 145 cm (1%) and an income of < regional minimum wage of Rp. 3.049.675 (66%). Based on pregnancy characteristics, the majority of respondents were multipara (74%), second-trimester gestational age (57%), and pregnant women who did not do Tetanus Toxoid immunization (76%). Of 31% of pregnant women had antenatal care about two times, and the check-up locations were in Private Practice Midwives (45%) and Public Health Center (40%). The majority of respondents did not have a history of infection (85%), but as many as 15% had a history of the disease (hypertension 7%, Asthma and heart 3%, lung and hypertension plus diabetes mellitus (1%). Most pregnant women do a Hb test (52%), of these figures it was found that 45% have normal Hb levels, moderate anemia was 4% and mild anemia 3%. Furthermore, as many as 88% of respondents did not have dietary habits, and found that as many as 88% of pregnant women consumed Fe tablets (83%), and only 17% did not consume them. Based on the deep interview, participants do healthy lifestyles such as consuming nutritious food, exercising, resting, and checking pregnancy. Furthermore, as many as 74% have high knowledge about stunting prevention efforts during pregnancy. Based on environmental observations, 85% of the home environment was clean, but respondents were in a smoker's environment (74%). All participants (15 people) stated that stunting is a condition of malnutrition in children, having less height, failing to grow or stunted growth, imperfect growth, and mothers with malnutrition that affect children. Women-empowerment and improving health care system are critical to mitigate stunting in children. Keywords: During pregnancy, prevention, risks of stunting